2021
DOI: 10.48550/arxiv.2103.17253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dirichlet Baths and the Not-so-Fine-Grained Page Curve

Kausik Ghosh,
Chethan Krishnan

Abstract: We present a doubly holographic prescription for computing entanglement entropy on a gravitating brane. It involves a Ryu-Takayanagi surface with a Dirichlet anchoring condition. In braneworld cosmology, a related approach was used previously in arXiv:2007.06551. There, the prescription naturally computed a co-moving entanglement entropy, and was argued to resolve the information paradox for a black hole living in the cosmology. In this paper, we show that the Dirichlet prescription leads to reasonable results… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…In the second part of the paper we used this dictionary to derive a formula for the mass of the graviton in the brane theory. The question whether graviton masses are important for the island formula has been discussed in [5,53,54]. One interesting observation to make is that apart from the near boundary limit, the formula for the graviton mass exhibits The solid line is computed numerically.…”
Section: Discussionmentioning
confidence: 99%
“…In the second part of the paper we used this dictionary to derive a formula for the mass of the graviton in the brane theory. The question whether graviton masses are important for the island formula has been discussed in [5,53,54]. One interesting observation to make is that apart from the near boundary limit, the formula for the graviton mass exhibits The solid line is computed numerically.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a great breakthrough towards the resolution of the black hole information paradox has been made [1,2], where double holography and island play an important role. See [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30] for some recent works. As a generalization of the AdS/CFT correspondence [31,32,33], double holography has a close relation to brane world theory [34,35,36] and AdS/BCFT [37,38,39,40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Second, replica wormhole saddle which is a wormhole connecting various copies of the original black hole. It was observed that the replica saddle leads to the contribution of the islands and enforces the entropy Furthermore, the island rule have been explored extensively for various black holes in flat and AdS spacetimes such as: JT gravity [9,[17][18][19][25][26][27][28], two-dimensional dilaton gravity [29][30][31][32][33] , in higher dimensions [33][34][35][36][37][38][39][40][41][42], higher derivative gravity theories [43], charged black holes [44][45][46][47], pure BTZ black hole microstates 3 [48][49][50], and black holes coupled to gravitating baths [50][51][52][53]. See also [4] for a very nice review on the topic.…”
Section: Introductionmentioning
confidence: 99%